Active Learning Training with Gamification-Based Learning Media to Improve Teacher Competence - Zumrotul Fauziah; Giati Anisah; Ahmad Manshur; Putri Dharma Yanti; Siti Nur Febriyanti (Universitas Veteran Bangun Nusantara, 2026)
ABSTRACT MA Islamiyah Malo faces several learning problems, including monotonous learning methods, limited teacher competence in creating interactive learning media, and low student involvement in the learning process. Based on these problems, this community service activity aims to increase the knowledge and competence of Madrasah Aliyah Islamiyah Malo teachers regarding Active Learning methods and the creation of Gamification learning media. The method used in this community service activity was Participatory Action Research (PAR) with a problem-solving approach and participation as a form of empowerment, including training and mentoring. The results of this community service activity were: first, an increase in MA Islamiyah Malo teachers' knowledge of how to apply active learning methods to involve students in the learning process. Second, this community service activity has equipped MA Islamiyah Malo teachers with the skills to create gamified learning media using several website-based applications such as Wordwall, Bamboozle, and Superteachertool. This activity solves problems at MA Islamiyah Malo, making students more actively involved in the learning process through interactive and engaging media, such as various fun games or activities. Keywords: Active Learning, Gamification, Teachers’ Competences.